One brave summer - Turner, Ann Warren; Turner, Ann Warren (New York : HarperCollins Publishers, 1995)
Katy spends the summer in the mountains with her mother, an aspiring writer, and learns a great deal about life from her adventurous new friend Lena May.
Keywords: Friendship -- Fiction; Fear -- Fiction; Authorship -- Fiction; Mothers and daughters -- Fiction